The mitochondrial copper chaperone COX11 has an additional role in cellular redox homeostasis. - Ivan Radin; Luise Kost; Uta Gey; Iris Steinebrunner; Gerhard Rödel (PLoS ONE)
Mitochondria are sites of cellular respiration, which is accompanied by the generation of dangerous reactive oxygen species (ROS). Cells have multiple mechanisms to mitigate the dangers of ROS. Here we investigate the involvement of the COX complex assembly chaperone COX11 (cytochrome c oxidase 11) in cellular redox homeostasis, using homologs from the flowering plant Arabidopsis thaliana (AtCOX11) and yeast Saccharomyces cerevisiae (ScCOX11). We found that AtCOX11 is upregulated in Arabidopsis seedlings in response to various oxidative stresses, suggesting a defensive role. In line with this, the overexpression of either AtCOX11 or ScCOX11 reduced ROS levels in yeast cells exposed to the oxidative stressor paraquat. Under normal growth conditions, both Arabidopsis and yeast COX11 overexpressing cells had the same ROS levels as the corresponding WT. In contrast, the COX11 knock-down and knock-out in Arabidopsis and yeast, respectively, significantly reduced ROS levels. In yeast cells, the ScCOX11 appears to be functionally redundant with superoxide dismutase 1 (ScSOD1), a superoxide detoxifying enzyme. The ΔSccox11ΔScsod1 mutants had dramatically reduced growth on paraquat, compared with the WT or single mutants. This growth retardation does not seem to be linked to the status of the COX complex and cellular respiration. Overexpression of putatively soluble COX11 variants substantially improved the resistance of yeast cells to the ROS inducer menadione. This shows that COX11 proteins can provide antioxidative protection likely independently from their COX assembly function. The conserved Cys219 (in AtCOX11) and Cys208 (in ScCOX11) are important for this function. Altogether, these results suggest that COX11 homologs, in addition to participating in COX complex assembly, have a distinct and evolutionary conserved role in protecting cells during heightened oxidative stress.